Does diabetes increase the risk of periodontitis? A systematic review and meta-regression analysis of longitudinal prospective studies - Nascimento, Gustavo G.; Leite, Fábio R. M.; Vestergaard, Peter; Scheutz, Flemming; López, Rodrigo (Acta diabetologica, 2018)
Aim Even though the association between diabetes and periodontitis is taken for granted, results on this association are conflicting within the literature. This systematic review assessed whether poorly controlled diabetes was associated with periodontitis onset or progression. Methods Electronic searches were performed in PubMed, Scopus and Embase databases. Hand search was carried out in the reference list of all articles included. Gray literature was investigated with a Google Scholar search. Prospective longitudinal studies on the association between diabetes and periodontitis were considered for this review. Studies should have presented at least two measurements of periodontal conditions over time. Data on study design, crude and adjusted estimates were collected. We used meta-analysis to estimate the pooled effect of hyperglycemia in people with diabetes on periodontitis onset or progression. Meta-regression and subgroup analyses were employed to investigate potential sources of heterogeneity between studies. Results Thirteen studies matched the inclusion criteria, comprising 49,262 individuals, including 3197 diagnosed with diabetes. Meta-analyses of adjusted estimates showed that diabetes increased the risk of incidence or progression of periodontitis by 86% (RR 1.86 [95% CI 1.3–2.8]). However, there is scarce information on the association between diabetes and periodontal destruction. Conclusions This study provides evidence that diabetes is associated with increased risk of periodontitis onset and progression in adults. Upcoming prospective longitudinal studies ought to overcome methodological caveats identified in this review.